External Communication of Institutions Providing Social Services during the COVID-19 Pandemic - Šumskienė, Egle; Banevičiūtė - Čirgelienė, Sigita (Socialinė teorija, empirija, politika ir praktika, 2022)
Crisis communication in social service organizations is an under-researched area. Nevertheless, this topic is very relevant, given the increasing threats to individuals and society. In the face of these threats, there is a growing need for effective communication in organizing and delivering social assistance. The outbreak of COVID-19 has changed interpersonal communication and the very nature of organizations’ work. This unprecedented situation has prompted an analysis of the level of preparedness of social services organizations to adapt in the long run to an acute, changed reality.This paper aims to investigate how daycare centers and residential care institutions were prepared to act during a crisis, with a particular focus on communication through the organization’s external channels – websites and social networks.The desk-based method was applied to analyze the external communication of 387 organizations providing social care and daycare services to children, the elderly, and persons with disabilities from all Lithuanian municipalities.In assessing the capabilities and responsibility of institutions providing social services to ensure consistent external communication, this study ranks alongside others that have examined social service provision practices during the COVID-19 outbreak. However, this study differs from others by highlighting the responsibilities of social workers in combating misinformation and fake news. The research emphasizes the need for consistent, continuous, clearly presented information. It identifies systemic and organizational gaps in the external communication skills of social service providers. It can be concluded that due to these gaps, social service provision institutions were unable to counterweigh fake news, which became “mainstream news” (Wiswanath et al., 2020) and posed a threat to public health, public safety, and human lives.The voice of social services’ providers was also missing in the wider socio-political context. Here, technological, legal, and political prerequisites emerged to address the knowledge gap and the technological exclusion of those at the margins of communication. Nevertheless, the study showed a lack of active participation of social service providers in this discourse, although they were closest to those experiencing the digital divide.The pandemic significantly adjusted the point of view on the importance of communication in social work, its goals and nature. The main weight has shifted from the pursuit of therapeutic goals toward technological, information dissemination, and risk management aspects.
Keywords: COVID-19; crisis communication; quarantine; social services